A grounded theory approach to the social and informational nature of business-it alignment - Pakarinen, Leo (2025)
An informational approach to the social dimension of Business-IT alignment using Grounded Theory to derive insights into the unresolved nature of alignment and the recent approaches to solving the issue. The goal of this thesis is to catalogue the recent research into Business-IT alignment with a focus on the social dimension and to derive future research directions by coding that data set to gain deeper insight into the issue. Grounded theory was chosen for its propensity to offer an avenue for emergent theorizations and the decision to focus on recent research was made based on the nature of Business-IT alignment as a saturated and unresolved field of research. The literature review reinforced the idea that Business-IT alignment includes operational level considerations and Social Capital Theory emerged to explain the realized strategy at the operational level. This implies implementing business and IT strategy in alignment is a more complex task than that of implementing a single strategy in terms of the social dimension, thus imposing a requirement for a degree of analysis of it for even the most mechanistic approaches. Future research directions can be proposed based on these emergent themes; In Business-IT alignment models the social dimension should be extended beyond the strategic level, which requires novel theorizations of strategic implementations on the operational level. The rigor of the fundamental models of the 1990s and early 2000s are undeniable, however they lack the richness of analysis required considering the complexity of contemporary technology, the use of which involves a human element. Keywords: Business-IT alignment, social dimension, grounded theory, knowledge-based view